2007
DOI: 10.1037/0022-3514.93.6.1028
|View full text |Cite
|
Sign up to set email alerts
|

Stereotypes help people connect with others in the community: A situated functional analysis of the stereotype consistency bias in communication.

Abstract: Communicators tend to share more stereotype-consistent than stereotype-inconsistent information. The authors propose and test a situated functional model of this stereotype consistency bias: Stereotypeconsistent and inconsistent information differentially serve 2 central functions of communicationsharing information and regulating relationships; depending on the communication context, information seen to serve these different functions better is more likely communicated. Results showed that stereotype-consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
136
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(145 citation statements)
references
References 40 publications
5
136
0
4
Order By: Relevance
“…As noted earlier, individuals seem to rely on the use of stereotypes in order to rapidly reaffirm shared bonds and knowledge during communication . For instance, Clark and Kashima (2007) demonstrated that the more stereotype-consistent information is perceived as socially connective, the more it is also used during communication. As such, it is clear that individuals select stereotypeconsistent information because it is subjectively considered as a tool for enhancing social connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…As noted earlier, individuals seem to rely on the use of stereotypes in order to rapidly reaffirm shared bonds and knowledge during communication . For instance, Clark and Kashima (2007) demonstrated that the more stereotype-consistent information is perceived as socially connective, the more it is also used during communication. As such, it is clear that individuals select stereotypeconsistent information because it is subjectively considered as a tool for enhancing social connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Research on how people establish common ground suggests that this use of negations is highly functional. People are more likely to talk about stereotypes and cultural knowledge that they think they share with other people even when counter-stereotypical information is available (Clark & Kashima, 2007;Fast, Heath, & Wu, 2009). This preference for the communication of stereotypes helps people to maintain and facilitate relationships and to feel socially connected (Clark & Kashima, 2007), and it facilitates the distribution of information about cultural phenomena (Fast et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…People are more likely to talk about stereotypes and cultural knowledge that they think they share with other people even when counter-stereotypical information is available (Clark & Kashima, 2007;Fast, Heath, & Wu, 2009). This preference for the communication of stereotypes helps people to maintain and facilitate relationships and to feel socially connected (Clark & Kashima, 2007), and it facilitates the distribution of information about cultural phenomena (Fast et al, 2009). As such, negations are an important functional linguistic mean by which stereotypes are interpersonally shared and maintained (Clark & Kashima, 2007;Fast et al, 2009; Maas, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, long-term and macro-level implications of micro-level dynamics are difficult to see without formal models or computer simulations. Experimental investigations have suggested that cultural information consistent with widely shared cultural information is more likely to be transmitted (e.g., Clark and Kashima, 2007); however, it takes a computer simulation model like Axelrod's (1997) to see that this process, which tends to enhance cultural convergence, can nonetheless generate global cultural diversity under some circumstances -even when globalizations are underway (e.g., Pfau et al, 2012). Nevertheless, without cross-temporal investigations, it is impossible to conclude whether cultural diversity is being maintained or cultural convergence is occurring.…”
Section: Complementarity Of Research Methodsmentioning
confidence: 99%